THE STUDY OF MARSHMALLOW'S PREFERENCES LEVEL WITH THE ADDITION OF GREEN GRASS JELLY (CYCLEA BARBATA L. MIERS) - Ahmad Sofyan; Esteria Priyanti; Kurnianingsih Kurnianingsih (University of Sultan Ageng Tirtayasa, 2020)
The purpose of this study is to determine the level of panelists’ preferences for green grass jelly marshmallows. The stages of the study consisted of two stages, which are making green grass jelly leaves extract and making green grass jelly marshmallows. The percentage of addition green grass jelly leaves extract as much as 25%, 50% and 75% based on the weight of the liquid needed in making marshmallows. This study uses a hedonic test that aims to determine the response of the panelists' preferences level to the taste, flavor, texture and color of green grass jelly marshmallows. The hedonic test results for the taste of green grass jelly marshmallows showed that products with the addition of green grass jelly leaves extract by 25% got the most preference from Panelist with mean score of 3.50 ± 0.73 (neutral). While the hedonic test results for the flavor, texture and color of green grass jelly marshmallows, showed that products with the addition of green grass jelly leaves extract by 50% got the most preference from Panelist with mean scores of 3.50 ± 0.68 (neutral), 3.50 ± 0.51 (neutral) and 3.30 ± 1.06 (neutral). Based on the results of determining the best product, panelists preferred marshmallows with the addition of green grass jelly leaves extract by 50%.